Identification Identifikasi Permasalahan UMKM Dodol di Kota Tangerang Selatan Untuk Mencapai Kriteria Produk Unggulan Pangan Daerah - Perak Samosir; Iyus Hendrawan; Yenny Widianty; Galih Mahessa Fitriadhy (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
According to data from the Ministry of Cooperatives and UKM of the Republic of Indonesia in 2023, the contribution of Micro, Small and Medium Enterprises (UMKM) to Gross Domestic Income (GDP) reached 61%. Based on the achievement of this contribution, UMKM in Indonesia have great potential to be developed so that they can increase their contribution to the national economy. Coaching and mentoring can be carried out through the relevant agencies in their respective regions. Considering that currently in various regions Food UMKM, especially snacks, are growing rapidly, several regions have made efforts to develop Food UMKM through activities to determine regional superior food products (PUPD). For this reason, PUPD criteria are needed for UMKM and it turns out that there are many problems faced by Food UMKM in trying to meet the PUPD criteria. One of them is Dodol UMKM in South Tangerang City. Through PUPD determination activities carried out by the South Tangerang City Department of Industry and Trade together with a team of experts from the Indonesian Institute of Technology, the problems faced by Dodol UMKM in South Tangerang City have been identified, namely labor citeria, renewables, facilities and technology.